Top 10 Myths about Migraine (Advancements in Homeopathic Research, 2022)
Migraine is a primary headache disorder characterized  by recurrent headaches that are moderate to severe.  Typically, the headaches affect one half of the head,  are pulsating in nature, and last from a few hours to  3 days. Associated symptoms may include nausea,  vomiting, and sensitivity to light, sound, or smell.
Keywords: Migraine; headache disorder; vomiting; Hormonal changes